Effect of water soaking and low temperature on panicum maximum seed germination / Nur Zakira Naqiyah Zulkefli - Zulkefli, Nur Zakira Naqiyah (Faculty of Plantation and Agrotechnology, 2018)
Panicum maximum is a perennial grass from family Poaceae that has economic value in various sectors. It is a valuable grass as it can be used as forages, to treat minor illnesses and also environmental pollution in wastewater. It is primarily propagated by seeds. However, the seeds of this grass have delayed germination. Seed dormancy is a condition where the seeds are unable to germinate under any condition including favorable environment. Previous researchers proposed that a dormant seed is unable to germinate during a certain period of time even when the normal physical environmental factors are favorable for its germination to occur. Therefore, seeds may be treated prior to germination for faster and uniform seed germination. This research was carried out to evaluate some practical procedures to enhance seed germination. Seed desiccation followed by water soaking, refrigeration and freezing treatments was tested for this purpose. Each treatment was replicated six times with 50 seeds per replicate. Another experiment on desiccation effects on seed germination was also carried out. Seed germination was carried out on moistened paper towel. The emergence of radicle was observed and recorded as seed germination. One way ANOVA was carried out using SPSS. The results indicate that the seeds could be germinated well without any water soaking, refrigeration or freezing treatments but seed desiccation was necessary to initiate germination. Overall seed germination was, however, low. Low fertilization and viable seed development may be the reason for low seed germination.